Upaya Meningkatkan Keterampilan Menyimak Menggunakan Media Audio Visual pada Peserta Didik Kelas V SDN 3 Selat Hilir Kabupaten Kapuas - Muhammad Rifa'i; Suniati Suniati (Bitnet: Jurnal Pendidikan Teknologi Informasi, 2018)
This study aims to improve learning outcomes and find out the learning activities of Indonesian by using Audio-Visual Media. The method used by the researcher was to use the Classroom Action research design of the subject in this study were all Vc grade students of SDN 3 Selat Hilir Kapuas Regency consisting of 22 students, 11 men, and 11 women. For data collection techniques used are observation and tests. The results of this study indicate that using Audio Visual Media can improve listening skills in Indonesian language learning in class Vc students of SDN 3 Lower Strait of Kapuas Regency. This is based on the results of the study with the acquisition of values in the learning activities that have been carried out for two cycles, it can be concluded that: the use of Audio Visual Media can improve students' listening skills, this can be seen from the pre-action average = 46.3 cycle averages I = 60 and cycle II = 95.4 with 100% classical completeness.